Dopant‐Free Organic Hole‐Transporting Material for Efficient and Stable Inverted All‐Inorganic and Hybrid Perovskite Solar Cells. Issue 16 (1st March 2020) - Jiang, Kui; Wang, Jing; Wu, Fei; Xue, Qifan; Yao, Qin; Zhang, Jianquan; Chen, Yihuang; Zhang, Guangye; Zhu, Zonglong; Yan, He; Zhu, Linna; Yip, Hin‐Lap
Abstract: Designing new hole‐transporting materials (HTMs) with desired chemical, electrical, and electronic properties is critical to realize efficient and stable inverted perovskite solar cells (PVSCs) with a p–i–n structure. Herein, the synthesis of a novel 3D small molecule named TPE‐S and its application as an HTM in PVSCs are shown. The all‐inorganic inverted PVSCs made using TPE‐S, processed without any dopant or post‐treatment, are highly efficient and stable. Compared to control devices based on the commonly used HTM, PEDOT:PSS, devices based on TPE‐S exhibit improved optoelectronic properties, more favorable interfacial energetics, and reduced recombination due to an improved trap passivation effect. As a result, the all‐inorganic CsPbI2 Br PVSCs based on TPE‐S demonstrate a remarkable efficiency of 15.4% along with excellent stability, which is the one of the highest reported values for inverted all‐inorganic PVSCs. Meanwhile, the TPE‐S layer can also be generally used to improve the performance of organic/inorganic hybrid inverted PVSCs, which show an outstanding power conversation efficiency of 21.0%, approaching the highest reported efficiency for inverted PVSCs. This work highlights the great potential of TPE‐S as a simple and general dopant‐free HTM for different types of high‐performance PVSCs. Abstract : A new S‐atom‐containing small molecule (TPE‐S) is introduced as a dopant‐free hole‐transporting layer in all‐inorganic and organic/inorganic hybrid perovskite solar cells (PVSCs) with a p–i–n inverted structure, leading to improved power conversion efficiencies of 15.4% and 21%, respectively. In addition, these devices also show enhanced photostability, with performance comparable to state‐of‐the‐art PVSCs based on the conventional n–i–p structure.